A Critical Study of the Hadiths on the Sense of Modesty of the Prophet Muhammad SAW in the Book Al-Shama'il Al-Muhammadiyyah by Al-Tirmidhi - Iqbal Al-Attas; Zulfahmi; Darsul S Puyu (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2026)
The book Al-Syamāʾil al-Muḥammadiyyah by al-Tirmidhi is a work that describes the physical characteristics, morals, and daily life of the Prophet Muhammad (peace be upon him). This research aims to provide a general description of the book, understand its compilation methods, and analyze the quality and authenticity of the hadiths regarding the Prophet's sense of modesty contained within it. Additionally, this study examines the content and implementation of these hadiths. The research employs a library research method with a qualitative approach that emphasizes data validity analysis and descriptive presentation. The findings indicate that Al-Syamāʾil al-Muḥammadiyyah consists of 56 chapters, one of which discusses the Prophet's sense of modesty, including two hadiths: the first hadith is classified as ṣaḥīḥ (authentic) and the second as ḍaʿīf (weak). The content of the hadiths shows that the modesty referred to is not a sign of mental weakness but rather an impulse to avoid bad deeds and actions that incur Allah's wrath. In conclusion, this research contributes to the study of hadith related to the Prophet's sense of modesty and inspires Muslims to emulate him.